The effects of race - Jablonski, Nina G.; Maré, Gerhard (Sun Press, 2018)
The STIAS research theme on Being Human Today explores the interrelated questions: What does it mean to be human? And: What is the nature of the world in which we aspire to be human? In the context of post-apartheid South Africa race and racism remain key references in both these questions. Why is this so, considering that the biological basis of race thinking has been refuted? Templates of race and racialism remain at the core of state policy in South Africa, periodic gross incidents of racism surface in public, and notions of the existence of races remain central to everyday thinking and discourse. This book is the result of the work of a group of leading thinkers and their in-depth conversations at STIAS during the winter of 2015 on the effects of race. Convened by evolutionary anthropologist Nina Jablonski and sociologist Gerhard Maré, the group included Njabulo Ndebele, Chabani Manganyi, Barney Pityana, Crain Soudien, Göran Therborn, Mikael Hjerm, Zimitri Erasmus and George Chaplin. The group reconvened annually through 2017. This is the first in a series of planned publications on the their work.